Improving the Physicochemical and Microstructural Qualities of Chicken Patties with the Addition of Red Beet Peel Flour (Beta vulgaris L) as a Filler - Herly Evanuarini; Agus Susilo; Dedes Amertaningtyas (Jurnal Ilmu-Ilmu Peternakan, 2023)
Chicken patties are one of the processed products that have a low fiber content and pale color, and are easily rancid because there are no added preservatives. This study aimed to determine the physicochemical and microstructural qualities of chicken patties using red beet peel flour (RBPF) as a source of fiber to increase the added value of RBPF. This research was conducted using experimental laboratory methods with a completely randomized design with 4 treatments and 4 replications. Treatment without the use of RBPF as a control (CP0), 1% (CP1), 2% (CP2), and 3% (CP3) used beetroot flour of the weight of material used. The variables measured were carbohydrates, texture, pH, fiber, organoleptic quality, and microstructure. Analysis of variance (ANOVA) was used as data analysis if there were differences in effect between the treatments, followed by Duncan's Multiple Range Test (DMRT). Using RBPF in chicken patties can improve the quality of chicken patties. The higher the use of RBPF, the higher the carbohydrate content, texture, and fiber, and lowered the pH of the patties. Panelists gave the highest rating score the higher the addition of RBPF in terms of color, taste, aroma, texture, and acceptability. The addition of RBPF with the best treatment was 3%. Based on the physicochemical quality, organoleptic quality, and microstructure, those addition has excellent nutritional content and RBPF which can be used to improve the texture of processed food products.